Analisis Jumlah Tenaga Kerja Optimal pada Proses Pengolahan Pisang Cavendish Guna Memenuhi Target Permintaan - Hidayat, Fauzan Rizky; Herlina, Herlina (SURYA TEKNIKA, 2025)
This study was conducted to determine the optimal number of workers in the Cavendish banana processing process at UD Queen Fruits, Mojokerto. The Stopwatch Time Study and Workload Analysis (WLA) methods were used to measure standard time and workload in each work center. The results showed that work center 3 (sorting and weighing) experienced the highest workload, with an average time of 160.84 seconds, while other work centers were much lower. This imbalance caused production delays and unfulfilled demand, especially for Queen Fruits products. WLA analysis showed that the ideal number of workers in work center 3 is two people, not one as is currently the case. Optimization through additional workers and workflow adjustments succeeded in increasing production capacity from an average of 44-47 boxes per day to 60 boxes. These findings indicate that work efficiency can be significantly improved through proper workforce planning.